1998
DOI: 10.7863/jum.1998.17.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer: can ultrasonography evaluate extent of disease?

Abstract: This study reviews the spectrum of sonographic findings in patients with gallbladder cancer, attempts to determine if sonography can identify patients with potentially resectable disease, and emphasizes the limitations of ultrasonography in the evaluation of ‐gallbladder cancer. Thirty‐five consecutive patients with histologically proven gallbladder carcinoma who had preoperative abdominal ultrasonography and surgery were identified. Involvement of the gallbladder and gallbladder fossa, metastases, bile ducts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Few studies have been published on the usefulness of US to determine tumor resectability [30,33,42,43]. Bach et al [30] compared US with intraoperative findings in 26 patients with GBC and found that US had an accuracy of 0.63 to determine the non-resectability of the tumor (Se: 0.94; Sp: 0.37; PPV: 0.56; NPV: 0.88).…”
Section: Ultrasound In Gbcmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have been published on the usefulness of US to determine tumor resectability [30,33,42,43]. Bach et al [30] compared US with intraoperative findings in 26 patients with GBC and found that US had an accuracy of 0.63 to determine the non-resectability of the tumor (Se: 0.94; Sp: 0.37; PPV: 0.56; NPV: 0.88).…”
Section: Ultrasound In Gbcmentioning
confidence: 99%
“…Few studies have been published on the usefulness of US to determine tumor resectability [30,33,42,43]. Bach et al [30] compared US with intraoperative findings in 26 patients with GBC and found that US had an accuracy of 0.63 to determine the non-resectability of the tumor (Se: 0.94; Sp: 0.37; PPV: 0.56; NPV: 0.88). US was useful to detect the primary mass and its spread to the liver but did not completely reflect the extent of the disease, and was especially limited in the localization of metastases to peritoneum and lymph nodes [30].…”
Section: Ultrasound In Gbcmentioning
confidence: 99%
See 2 more Smart Citations
“…Thisis in close agreement with thestudy ofOhtaniet al 19 where hepatic parenchymal involvement was found in 65% patients. Bach et al 20 described that ultrasonography is reliablein the detection of primary gallbladder mass. However, sonographic findings do not accurately reflect the full extent ofdisease and sonography is particularly limited in the diagnosis ofinvasion to the liver, lymph nodes, peritoneum etc.…”
Section: Histopathological Diagnosismentioning
confidence: 99%